[Hot Water Discharge Into Steam] - Streng, Evelyn Fiedler (1975)
Photograph of a hot water overflow turning into steam at a geothermal plant. A storage container stands to the left, consisting of a grey, stone base and central pillar, a blue, circular roof, and a round line of white pillars. It sits on a rock base behind a ditch full of water visible in the bottom right corner of the photograph. A round mountain is visible in the background with buildings sat on hills in front of it.